The psychological and philosophical typology of personality by René Le Senne as the foundation of personal and existential pedagogy by Janusz Tarnowski - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The analysis included the reception of René Le Senne’s theory of personality by psychology and pedagogy of the second half of the 20th century. The work reveals the extraordinary topicality of the typology in modern times, with still the observed lack of cooperation between psychologists and educators dealing with pedagogical axiology, the theory of upbringing and education. The typology survived thanks to the treatises of an outstanding scientist – Professor Janusz Tarnowski, whose dissertations in the field of personal-existential pedagogy of dialogue are reconstructed in this work and supplemented with philosophical interpretation by Tadeusz Gadacz in order to understand why the Le Senne’s typology is absent from social sciences and humanities as the basis for modern upbringing and self-education.